Optimising activity and participation outcomes for people with self-awareness impairments related to acquired brain injury: an interventions systematic review. Issue 2 (7th February 2019) - Engel, Lisa; Chui, Adora; Goverover, Yael; Dawson, Deirdre R.
ABSTRACT: Impaired self-awareness related to acquired brain injury (ABI-ISA) can result in limitations in daily living activities and community participation. We hypothesise that with the appropriate interventions, outcomes for adults with ABI-ISA can be enhanced. The objectives of the study were to describe and examine critically the non-pharmacological intervention literature and to identify intervention elements that optimise everyday living outcomes in adults with ABI-ISA. Two reviewers selected articles and extracted data using five databases, a review protocol, and systematic review standards (i.e., Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and Assessing the Quality and Applicability of Systematic Reviews (AQASR)). Included studies reported quantitative activity and participation intervention outcomes for people with stated or measured ABI-ISA, and the methodological quality of randomised controlled trials (RCT) was rated using the Physiotherapy Evidence Database scale (PEDro). Seventeen articles discussing 15 unique intervention studies were found, including two RCTs of good methodological quality. All studies reported improvements on measures of everyday living, utilised interventions with multiple therapeutic elements, and used various forms of external feedback. Evidence supports the use of intervention protocols including elements of experiential practice, external feedback, Socratic guided discussion, and metacognitive strategy training.